The role of Digital Elevation Models ( DEM) in Extracting Topographic characteristics in the Northwestern Sector of Libya (Journal of Libya for geographical studies, 2021)
The study deals with extracting some of the topographical characteristics of the area located in the Northwestern part of Libya, in the digital maps format. Also, the Digital Elevation Model (DEM) of the study area was done in order to use the surface analysis tools provided in Arc Map . The key findings of the study are as following: According to the height, the study area described as a high hill with the highest height reaching about 964m. Variation in the regression, as it ranged between flat to areas with steep slopes. Due to topography, the regression aspect of the study area was categorized into main and secondary aspect.
Keywords: Slope; Aspect; Hills hade; Contour; Digital Elevation Model